HARMONISASI INSTRUMEN ARAH KIBLAT - Hikmatul Adhiyah Syam; Subehan Khalik Umar (Universitas Islam Negeri Alauddin Makassar, 2020)
In the implementation of the prayer which is the most important obligation for Muslims, there are a number of conditions, harmony, sunnah, and etiquette as well as prohibitions that cannot be done in the worship. One of the legal requirements for prayer is facing the Qibla (Masjid Al-Haram) in Makkah City. This is based on the results of the agreement of the scholars, so the need for instruments to facilitate the position of determining the direction of Qibla. Qibla direction measurement instruments have developed more and more advanced, starting from the object that becomes a reference and systematic use of easy to short measurement time, including the Qiblat Tracker instrument with a Phone Tracker. However, the development of existing instruments needs to be considered how the method of use and the level of accuracy. So by testing the instruments at five mosque points directly measured through Google Earth, it was found 1º difference between the Qibla direction measurement results between Qiblat Tracker instruments that use celestial objects as objects and the Phone Tracker that makes the Star Walk 2 application as an object. This is because there is still a distance between the Tracker Phone instrument and the Star Walk 2 application. As a result, the Qiblat Tracker instrument is stated to be more accurate, it is necessary to know further how much deviation occurs between the Tracker Phone instrument against its own object.